Daniel X. 2 - Patterson, James, 1947-; Rust, Ned (Yen Press, 2011)
When Alien Hunter Daniel X attempts to stop an evil TV producer from creating chaos in Holliswood, he becomes the star of the tyrant's next spectacular film finale.